An Analysis of Crop Choice : Adapting to Climate Change in Latin American Farms - Seo, Niggol; Mendelsohn, Robert (World Bank, Washington, DC, 2012)
The authors explore how Latin American farmers adapt to climate by changing crops. They develop a multinomial choice model of farmer's choice of crops. Estimating the model across over 2,000 farmers in seven countries, they find that both temperature and precipitation affects the crops that Latin American farmers choose. Farmers choose fruits and vegetables in warmer locations and wheat and potatoes in cooler locations. Farms in wetter locations are more likely to grow rice, fruits, and squash, and in dryer locations maize and potatoes. Global warming will cause Latin American farmers to switch away from wheat and potatoes toward fruits and vegetables. Predictions of the impact of climate change must reflect not only changes in yields or net revenues per crop but also crop switching.